Gender and Degree Programs: The Interest for an Academic Field, a Factor that Influences the Choice of a Bachelors Degree - José Gamboa García; Rigoberto Marín Uribe (Universidad Autónoma de Baja California, 2009)
As part of a study on the expectations of benefit of higher education applicants, this article approaches the choice of a degree program according to the academic interest from the perspective of the rational analysis. Applicants who took the admissions test in two institutions were surveyed in order to carry out later statistical analysis with the purpose of finding a multivariate model. The obtained results showed that gender, work, and age were related to the applicants' interest on certain academic degree program. The interest for a degree program tends to be unimportant in employed women's choices, aged 20 years or older. Among applicants whose father considered higher education very important, the probability to consider one's interest on the choice of a bachelor's degree was higher for male applicants. The above information confirms the variation in rational calculations regarding social characteristics.